Caste, its twentieth century avatar - Srinivas, Mysore Narasimhachar (New Delhi : Viking ; New York, N.Y. : Penguin Books, 1996)
With reference to India; contributed articles.
Keywords: Caste -- India -- Social conditions; Caste -- Religious aspects; Women -- India -- Social conditions; India -- Scheduled tribes -- Government policy